Information Technology Capabilities, Organizational Agility, and Competitive Advantage: A Study of Micro, Small, and Medium Enterprises in Indonesia - Lovely Lovely; Ridhotama Shanti D. Ottemoesoe; Devie Devie (Master of Management, School of Business and Management, Petra Christian University, 2021)
This paper aims to explore the relationship between information technology (IT) capabilities and competitive advantage, with organizational agility as a mediator, in the case of micro, small, and medium enterprises engaged in the fashion industry in Indonesia. Data were collected by distributing questionnaires to 180 small to medium-sized enterprises in Indonesia’s fashion industry that have used e-commerce platforms to conduct their business activities. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) in SmartPLS 3.0 software. The study suggests that IT capabilities significantly influence organizational agility and competitive advantage. Therefore, the study can serve as a basis for the Indonesian government to promote digitalization and the use of e-commerce among micro, small, and medium enterprise owners in order to face changes in the market and remain competitive. It can also be beneficial for business owners and managers that aim to increase awareness of the importance of technology in their business operations. The work of this paper deepens the understanding of the relationship between IT capabilities, organizational agility, and competitive advantage, which are becoming increasingly important in the current digitalized and ever-changing business environment. It enriches the literature about micro, small and medium enterprise that is related to their IT capabilities level, how they use it to handle changes and factors that contributes in obtaining competitive advantage.